2012
DOI: 10.3746/jkfn.2012.41.10.1395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol Extracts from Zingiber officinale Rosc., Curcuma longa L., and Curcuma aromatica Salisb. on Acetylcholinesterase and Antioxidant Activities as well as GABA Contents

Abstract: This study investigated the cognition-related effects on antioxidant activities, γ-aminobutyric acid (GABA) contents, and AChE inhibitory activities in ethanol extracts from Zingiber officinale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…These changes might be due to swelling of the tick's body. The ethanolic C. longa extract might cause inhibition of the acetylcholinesterase activity as it contained high levels of polyphenols [39]. Consistent with the effects seen in the present study, Chaaban et al [40] observed that C. longa essential oil caused damage to the tick cuticles, midgut, and brain, and produced a fattening of the body of the third-instar Lucilia cuprina (Diptera: Calliphoridae) larvae.…”
Section: Discussionsupporting
confidence: 88%
“…These changes might be due to swelling of the tick's body. The ethanolic C. longa extract might cause inhibition of the acetylcholinesterase activity as it contained high levels of polyphenols [39]. Consistent with the effects seen in the present study, Chaaban et al [40] observed that C. longa essential oil caused damage to the tick cuticles, midgut, and brain, and produced a fattening of the body of the third-instar Lucilia cuprina (Diptera: Calliphoridae) larvae.…”
Section: Discussionsupporting
confidence: 88%
“…Phenolic compounds contained in foods have an antioxidant effect, and as such, they are expected to have a significant impact on improving memory function compromised by AD; this potential has been suggested by the findings of several studies (Kim et al, 2005;Orhan et al, 2004). AChE and BChE have been performed by Korean research groups, including: comparative analysis of the AChE inhibitory activities of edible plant extracts, including Angelica gigas and Siberian ginger (Jung et al, 2012a;2012b); analysis of the AChE inhibitory effects of green, puer, oolong, and black teas sold in Korea (Jeong et al, 2009); analysis of the AChE inhibitory effects of ginger, turmeric, and garlic (Jung et al, 2012a;2012b). Although these studies analyzed the AChE inhibitory effects of edible plants, most studies have been limited to medicinal plants.…”
Section: Introductionmentioning
confidence: 99%